The Middle East journal
The Middle East Institute has published The Middle East Journal quarterly since 1947. The Journal provides original and objective research and analysis, as well as source material, on the area from Morocco to Pakistan and including Central Asia. The Journal provides the background necessary for an understanding and appreciation of the region's political and economic development, cultural heritage, ethnic and religious diversity.